Analysis Of Development Policy On The Serang-Panimbang Toll Road In Banten Province During The COVID-19 Pandemic - Agus Mufariq; Sinta Ningrum; Ira Irawati; Ida Widianingsih (Universitas Padjadjaran, 2022)
The construction of the Serang-Panimbang Toll Road is intended to increase the accessibility of South Banten and support the economy in the Tanjung Lesung Special Economic Zone (SEZ) in accordance with Government Regulation No. 26 of 2012 concerning the Tanjung Lesung Special Economic Zone (SEZ), as well as to support the acceleration of the expansion of national economic development. During the Covid-19 pandemic, there was a massive change in the way people live, and the government needed to adjust it in all fields, including the construction of the Serang Panimbang toll road. Problems began to emerge in adjusting development policies to the conditions of the COVID-19 pandemic. This article will discuss in more depth the policy analysis of the Serang-Panimbang toll road construction in Banten Province during the Covid-19 Pandemic and the differences between before and after the pandemic. This study uses a descriptive qualitative approach. In collecting data, this research uses observation, interviews, literature study, and internet searching. Data collection in this study was carried out by studying the existing literature. This article analyzes the benefits that will be obtained by the community with CBA analysis using Pareto efficiency.